Analisis Kinerja Piutang Perusahaan Sebelum dan Masa Pandemi Covid-19 (Studi pada Sub Sektor Kesehatan yang Terdaftar di BEI) - Wafi Yahya; Widya Rizki Eka Putri; Sari Indah Oktanti Sembiring (Departement of Mathematics Education, 2024)
This investigate looks at contrasts within the execution of receivables turnover in pharmaceutical segment companies some time recently and amid the Covid-19 widespread. The populace in this inquire about are pharmaceutical companies recorded on the Indonesian stock trade from 2018 to 2021. The test utilized in this investigate is the matched test t test. The comes about of this investigate are that there are contrasts in receivables turnover execution as measured by Receivable Turnover in pharmaceutical companies some time recently and amid Covid-19.